2022
DOI: 10.3390/biology11071006
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Consequences of Electrolyte Disturbances in Domestic Animals

Abstract: Electrolyte balance is essential to maintain homeostasis in the body. The most crucial electrolytes are sodium (Na+), potassium (K+), magnesium (Mg2+), chloride (Cl−), and calcium (Ca2+). These ions maintain the volume of body fluids, and blood pressure, participate in muscle contractions, and nerve conduction, and are important in enzymatic reactions. The balance is mainly ensured by the kidneys, which are an important organ that regulates the volume and composition of urine, together with which excess electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Our finding declared that furosemide showed a significant decrease in serum Sodium (Na), Potassium (k), and Magnesium (Mg)levels and a non-significant change in Calcium (Ca), and (Mg) levels. Moreover, these findings concur with those of Muller et al (2015), who reported that patients receiving furosemide as an anti-hypertensive medication had deficiencies in their levels of calcium, magnesium, Cl, and Na, and also support the findings of Gałęska et al (2022), who declared how furosemide-treated diabetic cats had down-regulated blood electrolyte levels. These findings are attributable to furosemide's action on the renal tubule, which is to be expected given that it is known to inhibit membrane Na+-K+-ATPase activity (Iacobelli and Jean-Pierre, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Our finding declared that furosemide showed a significant decrease in serum Sodium (Na), Potassium (k), and Magnesium (Mg)levels and a non-significant change in Calcium (Ca), and (Mg) levels. Moreover, these findings concur with those of Muller et al (2015), who reported that patients receiving furosemide as an anti-hypertensive medication had deficiencies in their levels of calcium, magnesium, Cl, and Na, and also support the findings of Gałęska et al (2022), who declared how furosemide-treated diabetic cats had down-regulated blood electrolyte levels. These findings are attributable to furosemide's action on the renal tubule, which is to be expected given that it is known to inhibit membrane Na+-K+-ATPase activity (Iacobelli and Jean-Pierre, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Vanadium was reported by Wilk et al11 to have harmful effects on both reproductive and developmental health. Cesium mimics the potassium in the body12, and having excess cesium can lead to hypokalemia13 which affects fertility in both males and females14.…”
Section: Discussionmentioning
confidence: 99%
“…Vanadium was reported by Wilk et al [11] to have harmful effects on both reproductive and developmental health. Cesium mimics the potassium in the body [12] , and having excess cesium can lead to hypokalemia [13] which affects fertility in both males and females [14] . The results reveal the recuperating effect detoxication using the modern Mayr therapy on heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physiological processes depend on calcium. Calcium (Ca) plays an important role in blood clotting, membrane permeability, nerve conduction, muscle contraction, enzyme activity, and hormone secretion [ 42 , 43 ]. The concentration level of Ca in Viscum spp.…”
Section: Potential Of Viscum Species As a Source O...mentioning
confidence: 99%